Pengaruh Penerapan Teknologi Smart Traffic Management terhadap Efisiensi Lalu Lintas dan Emisi Karbon - Hafram, Siti Maryam; Putra, Wudi Darul (Syntax Corporation, 2025)
This study aims to analyze the effect of the application of Smart Traffic Management (STM) technology on traffic efficiency and carbon emissions on Jalan A.P. Pettarani, Makassar City, by using a field data collection method before and after the implementation of STM which includes the average speed of vehicles, travel time, and traffic volume. The results showed that after the implementation of STM, the average vehicle travel time was reduced from 25 minutes to 20 minutes, reflecting a significant decrease of 20%, while the waiting time at major intersections was also reduced by 35%, indicating an increase in vehicle flow during peak hours. In addition, carbon emissions data shows a decrease from 180 grams per km to 148 grams per km per vehicle, which means an 18% reduction in carbon emissions due to reduced vehicle idle time and smoother traffic flow. This study also identifies challenges in the implementation of STM, such as limited telecommunication infrastructure and lack of socialization to road users, and provides recommendations for local governments to integrate STM technology with public transportation policies to support sustainable development and improve the quality of urban transportation systems.